SEPERANGKAT ALAT SALAT SEBAGAI MAHAR: SIMBOL KESALEHAN ATAU REFLEKSI KETIMPANGAN GENDER? - Al Umam, Ahmad Hafidh; Ilmiati, Ilmiati (IAIN BONE, 2025)
This study investigates the common practice of giving a set of prayer equipment as a dowry (mahar) in marriage traditions in Bengkak Village, Indonesia. While the dowry in Islam is intended as a form of honor and protection for women, its symbolic interpretation in local customs may overshadow its functional role. The research explores whether such a practice reflects genuine piety or reproduces gender inequality. This qualitative descriptive research employed a combination of literature review and semi-structured interviews with community members, including brides, grooms, religious leaders, and local elders. Data were analyzed thematically to identify both the cultural symbolism and the socio-legal implications of the dowry practice. The results show that while the set of prayer equipment is symbolically tied to ideals of religiosity and marital harmony, it often fails to provide material security for women, particularly in cases of divorce. Negotiations over dowry value and form are frequently limited by tradition, leaving little space for women to advocate for more substantial or economically protective dowries. The study is context-specific to Bengkak Village and may not fully capture dowry practices in urban or more economically diverse settings. The reliance on qualitative data limits generalizability but offers rich insights into local perceptions and gender dynamics. By linking religious symbolism with gender justice analysis, this study contributes to the discourse on how Islamic marital practices can be reinterpreted to promote both spiritual meaning and equitable protection of women’s rights. It highlights the need for community awareness to negotiate dowries transparently and fairly.